2008
DOI: 10.1016/j.rmed.2008.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Common predictors of smoking cessation in clinical practice

Abstract: Although smoking cessation is clearly beneficial, many smokers respond poorly to smoking cessation efforts with rather disappointing overall success rate of long-term abstinence. The perceived lack of effectiveness of smoking cessation may well influence how physicians set their priorities with regard to an effective use of their consultation time. Negative beliefs and attitudes can be resolved by advancing the general understanding of the natural history of quitting, by making sensible use of smoking cessatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
191
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 195 publications
(213 citation statements)
references
References 110 publications
17
191
3
2
Order By: Relevance
“…An unfavourable effect of older age for successful quitting was found at the limit of statistical significance in the class with the higher GN-SBQ, suggesting that, with regular repetitions of rituals associated with cigarette smoking over the years, the influence of behavioural dependence could become more prominent than physical dependence. Initial motivation levels to stop smoking can predict success with smoking cessation [22,23]. It was also shown that success rates in participants with low GN-SBQ scores appeared to be markedly dependent on their level of motivation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An unfavourable effect of older age for successful quitting was found at the limit of statistical significance in the class with the higher GN-SBQ, suggesting that, with regular repetitions of rituals associated with cigarette smoking over the years, the influence of behavioural dependence could become more prominent than physical dependence. Initial motivation levels to stop smoking can predict success with smoking cessation [22,23]. It was also shown that success rates in participants with low GN-SBQ scores appeared to be markedly dependent on their level of motivation.…”
Section: Discussionmentioning
confidence: 95%
“…It classifies motivation to quit according to four possibilities of success: 1) it is not the time to quit (,6), 2) discrete (6-12), 3) good (12)(13)(14)(15)(16), and 4) very good (.16). The GN-SBQ (Appendix 2) consists of 11 items and classifies behavioural dependence according to quartiles: mild (,12), moderate (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), strong (23-33) and very strong (.33). In addition, levels of eCO were measured using a portable device (Micro CO; Micro Medical Ltd, Rochester, UK).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…A brief consultation and behavioral support of a health professional are effective in providing motivation to kick the habit, as demonstrated by Caponnetto and Polosa 13 . The addition of drugs and nicotine replacement therapy to behavioral therapy, produces higher success rates when compared with therapies employed in a disjointed manner or in cases of unassisted cessation of smoking 11 .…”
Section: Discussionmentioning
confidence: 98%
“…All smokers are dependent on nicotine to some degree. In cases of high levels of nicotine dependence, smokers tend to experience intense withdrawal symptoms, reinforcing the need for treatment with drugs during the first few weeks of abstinence 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Several predictors of success in smoking cessation can be used to identify probable relapsers, including late age of initiation of cigarette smoking, longer duration of previous quit attempts, lack of depression, low-to-moderate nicotine dependence, absence of alcohol problems, sustained level of motivation, being married, and not having any other smokers in the household [21]. Identification of individual characteristics that predict success in smoking cessation is highly desirable as this could help to match smokers with a strategy that is more likely to help them quit, to identify smokers who might need more intensive treatment, and to make the most of health care resources.…”
Section: Notes On Relapse Preventionmentioning
confidence: 99%